Deception in Conversation: The Study of Prince Andew’s Inteview About Jeffrey Epstein Sexual Allegations - Sofista Lilla Saferia (English Education:Journal of English Teaching and Research, 2021)
Implicature as one of the prominent element of the principles has been developed in lateststudies, mainly the objective as it could be utilitizes to deliberately deceive the listeners onoccasion. Previous researches has shown how speaker could deceive listener despite notsay something untrue or lie by categorizing lie is not something that is said but what isimplied in conversation. This study aims to investigate implied meaning and deceivingstatements in conversation. The object of this study is Prince Andrew’s BBC Newsnightinterview about his involvement with convicted sex offender, Jeffrey Epstein. The data useddocument analysis based on the interview video of Prince Andrew’s interview with EmilyMaitlis. The result of this study indicates that Prince Andrew’s implied statements showdeeper relationship and more involvement with Jeffrey Epstein than what he was trying tosay in the interview.